Association between urinary polycyclic aromatic hydrocarbon metabolites and diabetes mellitus among the US population: a cross-sectional study. Issue 2 (25th June 2022) - Mallah, Manthar Ali; Basnet, Til Bahadur; Ali, Mukhtiar; Xie, Fuwei; Li, Xiang; Feng, Feifei; Wang, Wei; Shang, Pingping; Zhang, Qiao
Abstract: Background: The primary aim of this study is to examine the association between urinary polycyclic aromatic hydrocarbons (PAHs) and diabetes mellitus (DM) among the US population. Methods: We used data from the National Health and Nutritional Examination Survey 2003–16, which is a nationally representative population-based survey of the US non-institutionalized population. Logistic regression analysis was performed to evaluate the association between urinary PAHs and the prevalence of DM using odds ratios (ORs) and 95% confidence intervals (CIs). Results: The study sample including 13 792 individuals ≥18 y of age. The average ages of the three PAH tertiles were 42.56±19.67, 42.21±19.51 and 43.39±17.99 y. An increased risk of DM was found with increased odds for the second (OR 1.56 [95% CI 1.36 to 1.79]) and third tertile (OR 1.79 [95% CI 1.55 to 2.06)] of urinary PAH as compared with the first tertile. Similarly, higher chances of DM were observed in the second (men: OR 1.42 [95% CI 1.18 to 1.71]; women: OR 1.76 [95% CI 1.44 to 2.14]) and third tertile (men: OR 1.69 [95% CI 1.38 to 2.08]; women: OR 1.79 [95% CI 1.46 to 2.19]) of urinary PAHs as compared with the first tertile in both men and women. Conclusions: A population-based cross-sectional study found a positive association between urinary PAHs and DM in the US population.